2010
DOI: 10.1007/s10750-010-0204-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of groundwater withdrawal and land use changes on brook charr (Salvelinus fontinalis) thermal habitat in two coldwater tributaries in Michigan, U.S.A.

Abstract: Brook charr (Salvelinus fontinalis) is a sentinel fish species which requires clean, cold water habitats. As such, many jurisdictions in the United States where brook charr are present use this species as an indicator of ecosystem health. In Michigan, groundwater-dominated streams are currently being impacted by increased groundwater withdrawal and land use/land cover changes which alter stream temperatures and their flow, and thus have the potential to significantly influence brook charr production and behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Our conclusions are consistent with other studies in Upper Midwest watersheds such as those by Waco & Taylor (2010) who found that conversion of forest to pasture would result in very minor shifts in stream temperature. However, based on the relatively high amount of baseflow in this stream (65%), the groundwater aquifer supplied this stream with water temperatures that can support brook charr populations throughout the year.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our conclusions are consistent with other studies in Upper Midwest watersheds such as those by Waco & Taylor (2010) who found that conversion of forest to pasture would result in very minor shifts in stream temperature. However, based on the relatively high amount of baseflow in this stream (65%), the groundwater aquifer supplied this stream with water temperatures that can support brook charr populations throughout the year.…”
Section: Discussionsupporting
confidence: 93%
“…In groundwater-dominated brook charr streams, it is imperative to evaluate the effects of aquifer withdrawal for human use in the light of brook charr production (Waco & Taylor 2010). Identification of the key mechanisms controlling cold water delivery and maintenance in brook charr streams is a fundamental step in the effective management of this cold water-reliant species.…”
Section: Management Implicationsmentioning
confidence: 99%
“…2008; Kanno et al. 2010; Waco and Taylor 2010). The populations surveyed in this study are under the same anthropogenic threats due to the proximity of the TLH which crossed 20 watersheds in its Phase II section (Red Bay to Cartwright) alone (Jacques Whitford Environment Limited 1998).…”
Section: Discussionmentioning
confidence: 99%
“…2008; Kanno et al. 2010; Waco and Taylor 2010). Second, fishing pressure may increase as lakes become more easily accessible; previously, the majority of the lakes in Labrador were accessible by float plane only.…”
Section: Introductionmentioning
confidence: 99%
“…Brook trout have been lost from over 50% of the historical habitat in Connecticut, USA, (Hudy et al 2008), and lotic populations are primarily located in small, cold headwater streams (Kanno and Vokoun 2008). Land development and resulting habitat alteration has often been associated with population declines (Kanno et al 2010;Stranko et al 2008;Waco and Taylor 2010), and climate change raises concern for the persistence of this steno-thermal species (Chu et al 2008;Flebbe et al 2006).…”
Section: Introductionmentioning
confidence: 99%